Adherence to Antiretroviral Therapy (ART) Amongst black adolescents. A case study on the perceptions of HIV/AIDS adolescent male patients in Ekurhuleni, South Africa - Monyai, Bradley Mothusi (University of the Witwatersrand, Johannesburg, 2024)
South Africa continues to upscale in the advancement of programmatic interventions towards HIVand AIDS, however, this epidemic is observed to be affecting a high proportion of adolescents and exacerbates critical social, psychological, economic, and educational challenges (Poku & Poku, 2020). In the estimated 7.8 million of South Africans living with HIV, the second highest prevalence rate is considered to be amongst black adolescent males. Within this cohort, adolescent males reported high risky sexual behaviours related to HIV. moreover, in their adolescent-hood, HIV risk factors were correlated with lower levels of HIV and AIDS related information, low rates of viral suppression and condom attitudes. There is a noted inconstant adherence to ART (Anti-Retroviral Therapy) amongst adolescent males. Such being the case, drivers of non-adherence, retention in care that is poor and mental health challenges differs with each adolescent demographic background and the mode of infection. Such notable variances indicates that studies which merge adolescent males and their counterparts living with HIV may blur social, psychological, structural, and clinical experiences of these two diverse sub-populations. This qualitative research study aimed to explore adherence to antiretroviral therapy amongst black adolescent males living with HIV. A qualitative case study design was employed and twelve adolescent males from Ekurhuleni health care facilities were purposely sampled in the study. The data collection method that was used, was a semi structured focus group and face to face interviews whereby an interview and a focus group schedule were utilised. The different themes that emanated from the participant’s experiences were analysed using thematic content analysis. Major findings highlight that, societal stigma profoundly impacts self-perception, leading to a pervasive sense of shame and low self-worth among black adolescent males, influencing their reluctance to disclose their HIV status. The intersectionality of identity, encompassing socioeconomic factors, sexual orientation, and race, intricately intersects with health status, illuminating the challenges faced by economically disadvantaged adolescent males managing a chronic health condition. Moreover, the intricate dynamics of HIV status disclosure within families contribute to adolescent fears of social isolation, exacerbated by poor support for medication routines. Lastly, challenges in healthcare accessibility and patient experience, characterised by discomfort with healthcare facilities and dissatisfaction with human interactions, underscored the need for a more patient-centric approach and comprehensive interventions to address systemic barriers.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Social Development to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Adolescent; HIV and AIDS; Adherence to ART; Retention in care; Mode infection; SDG-3: Good health and well-being